Construction performance guarantee : performance bond / Awang Ihsan Awang Yunus and Khairul Anuar Maarof - Awang Yunus, Awang Ihsan; Maarof, Khairul Anuar (Faculty of Architecture, Planning and Surveying, 2013)
Nowadays in the construction industry, the problems of non-performance by the contractor have become a common thing faced by the client. This problems usually happens the contractor failed to execute the according the contract. It has been a common issue in Malaysia when dealing with contractor's non-performance. Thus the client needs a protection in the event when the Contractor fails or defaults in its performance under the contract, such as abandonment or the works is of proof or any defects in the work appearing during the defects liability period. Contractor's performance guarantee is the feature or a management tool to handle the risk of non-performance by the contractor. Performance bond are introduced to ensure that contractor will honour and perform the contractor diligently. If the contractor failed to execute the work within the specification of the contract or the contractor abandoned the work, the performance bond can be used towards the disbursement of expenses incurred by the employer in rectifying the defect. Performance bond is three party agreement between the employer, contractor and a third party (usually a bank or insurance company), who agrees to pay sum of money to the employer, the event of default by the contractor in the construction contract. If the contractor has performed in the contract or in the words, has carried out the work within the contract, the client needs to release back the performance bond.